Gross Morphometrical Studies on the Testes of Dog During Different Seasons - Gayatri M. Gadariya,; Vishnudeo Kumar,; Anil Sharma,; R. H. Bhatt,; R. J. Padodara, (Indian Journal of Veterinary Anatomy, 2026)
The present study was conducted on the testes of 18 adult dogs (mean body weight 20.28 ± 0.65 kg)during the summer, monsoon and winter seasons. Thirty-six (36) numbers of testes were collected, 12 in eachseason, from dogs operated for neutering at the Veterinary Hospital of Municipal Corporation. Gross anatomicaland biometrical observations on testicular weight, volume, length, width, thickness and circumference wererecorded. The paired testes were located in the scrotum halfway between the anus and the inguinal region. Insidethe scrotum, the visceral layer of tunica vaginalis covered the testis and epididymis. The testes had their long axesoriented obliquely with a dorso-caudal direction. The reddish-coloured, roughly oval-shaped testes had twosurfaces: lateral and medial, two borders: dorsal and ventral and two ends: proximal and distal. The epididymiswas attached dorso-laterally to the testis. The seasonal effect was significant (p